Mental health literacy among older adults in Shanghai: a descriptive qualitative study - Rongjing Xu; Mingrui Jing; Aining Zhang; Liqi Zha; Yan Wang; Anni Wang; Jun Tang; Biyun Xia; Shoumei Jia (Frontiers in Psychology)
BackgroundThe aging population in China is surging rapidly, and elderly individuals are at higher risk of multiple mental health issues. Improving the mental health literacy of older adults can help them recognize mental illness and adopt proactive measures, potentially improving their mental health status and supporting the goal of healthy aging.ObjectiveTo explore mental health literacy among older adults, providing a foundation for future interventions aimed at improving their mental health literacy.MethodsGuided by the new conceptualization framework of mental health literacy developed by Jiang et al. the study involved 20 community-dwelling older adults from four communities in Shanghai who were selected through purposive sampling to participate in semi-structured interviews. Thematic analysis was employed to summarize and extract themes from the data.ResultsThe qualitative analysis identified three primary themes and eight subthemes: inadequate knowledge about mental health and illnesses, negative intentions and attitudes toward maintaining mental health and preventing mental illnesses, and health behavior to promote mental health and prevent mental disorders.ConclusionThis study reveals significant gaps in mental health literacy among older adults, underscoring the necessity for multifaceted interventions. It calls for concerted efforts from individuals, families, and society to bolster mental health knowledge, challenge stigma, and encourage supportive behaviors. By integrating these approaches with the ‘Healthy China 2030’ policy, we aim to enhance mental health literacy for the aged.